Modified zeolite as a catalyst for Pongamia pinnata oil esterification in biodiesel production. (2017) - Nilavunesan, D.; Thiruvengadaravi, K.V.; Yuvarani, M.; Sivanesan, S.
The solid acid catalyst, Nb/P/ZSM-5 was synthesised and characterised for its nature and morphological features. The catalyst was employed in the esterification of free fatty acids in Karanja (P. pinnata) oil for biodiesel production. Parameters affecting the P. pinnata oil esterification were determined and Nb/P/ZSM-5 catalyst esterified P. pinnata oil was analysed using spectroscopic investigation.